2019
DOI: 10.1021/acs.molpharmaceut.9b00470
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Cellular Uptake, Cytotoxicity, and Cellular Death Modality of Phospholipid-Coated Gold Nanorods toward Breast Cancer Cell Lines

Abstract: Gold nanorods (GNRs) have gained pronounced recognition in the diagnosis and treatment of cancers driven by their distinctive properties. Herein, a gold-based nanosystem was prepared by utilizing a phospholipid moiety linked to thiolated polyethylene glycol, 1,2-distearoyl-sn-glycero-3-phosphoethanolamine-N-PEG-SH, as a surface decorating agent. The synthesized phospholipid-PEG-GNRs displayed good colloidal stability upon exposure to the tissue culture medium. Cytotoxicity of phospholipid-PEG-GNRs was investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 72 publications
3
23
0
Order By: Relevance
“…These genes interact with other regulatory factors such as the p53 family and regulate the apoptotic pathways [52]. These results are in line with our previous study, which demonstrated that GNR (A) significantly upregulated the expression of TP53BP2 in the MCF-7 breast cancer cell line and modulated the expression of other regulatory genes involved in several apoptotic pathways [25].…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…These genes interact with other regulatory factors such as the p53 family and regulate the apoptotic pathways [52]. These results are in line with our previous study, which demonstrated that GNR (A) significantly upregulated the expression of TP53BP2 in the MCF-7 breast cancer cell line and modulated the expression of other regulatory genes involved in several apoptotic pathways [25].…”
Section: Discussionsupporting
confidence: 90%
“…The anti-angiogenic effect of GNR in this study strongly supports their proposed anti-cancer activity towards breast cancer cell lines reported in previously published studies [24,25]. It is worth mentioning that although GNR (A) showed a significant anti-angiogenesis effect and high mortality rate toward embryos, their anti-cancer activity against breast cancer cells was observed even at concentrations much lower than that utilized in the current angiogenesis and embryogenesis studies [24,25].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations